Analisa Waste Material Konstruksi Dengan Menggunakan Metode Lean Construction Studi Kasus : Pekerjaan Pembangunan Puskesmas Purwodadi Kabupaten Tanjung Jabung Barat - Yuniar, Riana; Handayani, Elvira; Amalia, Kiki Rizky (Universitas Batanghari, 2023)
Material is one component of the cost that plays an important role in supporting the success of a project. In the implementation of building construction projects, leftover materials or Construction Waste cannot be avoided. Excess material, whether from work results or from construction materials that are left/scattered/destroyed and cannot be used again, is called construction waste. Thus, a method is needed for the efficiency of remaining construction materials (Intan et. Al,2005). Construction in Indonesia currently has many problems regarding inefficiency in the implementation of construction. The causes of this inefficiency include poor performance, waste of resources used during the construction process, but this does not add value to the function of the resources used. Based on data submitted by the Lean Construction Institute (LCI), waste in the construction industry is around 57% and activities that provide added value are only 10% (Abduh, 2007). In construction projects, problems are often found in the construction process, such as changes to project drawings, changes to specifications, poor storage, and other technical problems in the field that cause material waste. Problems like this can have an impact on project cost losses beyond what was planned.Lean Construction is very necessary in construction projects so that waste does not occur due to the problems that have been explained previously, it is hoped that it can reduce waste on the project. So that it can reduce costs caused by waste and can establish better relationships between individuals involved in the project.